2011
DOI: 10.1155/2011/845957
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Energy Efficient Curve: Gate Sizing for Minimum Power under Delay Constraints

Abstract: A design scenario examined in this paper assumes that a circuit has been designed initially for high speed, and it is redesigned for low power by downsizing of the gates. In recent years, as power consumption has become a dominant issue, new optimizations of circuits are required for saving energy. This is done by trading off some speed in exchange for reduced power. For each feasible speed, an optimization problem is solved in this paper, finding new sizes for the gates such that the circuit satisfies the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In [35][36][37], some approaches are proposed for transistor sizing considering delay constraints with the least power consumption. Two methods are presented to reduce power in [38].…”
Section: Related Workmentioning
confidence: 99%
“…In [35][36][37], some approaches are proposed for transistor sizing considering delay constraints with the least power consumption. Two methods are presented to reduce power in [38].…”
Section: Related Workmentioning
confidence: 99%
“…By this means, dynamic effective capacitance C dyn could be reduced when gates are downsized. By selectively downsizing the gates of a circuit, Aizik and Kolodny [18] demonstrated that dynamic and leakage energy dissipations can be reduced. Doing so, however, may lead to an increase in speed delay.…”
Section: Downsizing Gatesmentioning
confidence: 99%